DEVELOPING PLANTAE ATLAS FOR PLANT IDENTIFICATION AND BASIC SCIENCE PROCESS SKILLS TRAINING - Nanda Wardhani; Endang Susantini; Ahmad Bashri (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2019)
Abstract Science process skills are thinking skills in problem solving and planning research in order to gather scientific information. Therefore this research will train basic science process skills, namely the skills of observing, classifying, predicting and asking questions as well as for means of identifying plants.The purpose of this study were to produce the Plantae Atlas for the means of plant identification, to train basic science process skills and to describe the validity of theoretical and empirical feasibility. This research trained the basic science process skills how to observe, classify, predict and ask a question. This developmental research produced the Plantae Atlas that were limited tested at SMAN 19 Surabaya with a total of 15 students of class X MIA 4. Data collection in this study used validation, observation and questionnaires methods. The results of this study indicated that the theoretical feasibility of validation was 93% which was categorized as very feasible. The empirical feasibility reached a score of 92% which was categorized as very good. Student response positively by 98% which was categorized as very feasible. Thus Plantae Atlas cocluded as feasible theoretically and empirically. Keywords: Plantae Atlas, basic science process skills, Plantae, theoretical, empirical